2020
DOI: 10.3233/ies-201150
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic testing of muscle strength in older adults with knee osteoarthritis: An integrative review

Abstract: BACKGROUND: Knee osteoarthritis (OA) is common among older adults and associated with impaired knee strength. OBJECTIVE: Describe isokinetic testing procedures and clinimetric findings associated with the testing of knee strength in the presence of knee OA. METHODS: Relevant articles were identified by an electronic search of PubMed using the search string "isokinet * AND knee osteoarthritis." RESULTS: One-hundred and twenty-nine relevant articles were found. The articles support the validity and reliability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Hence, it is plausible that strength deficits, especially in the quadriceps, may also occur in degenerative meniscal tear cohorts, a group known to have an increased risk of developing OA. In this context, isokinetic dynamometry is one of the most reliable and widespread approaches to assessing muscle strength [16]. Using this approach, we found no significant difference in concentric knee flexor or extensor (body weight adjusted) strength between groups at a velocity of 60 • /s and 180 • /s which can be explained by the rather short duration of the intervention program (6 weeks).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Hence, it is plausible that strength deficits, especially in the quadriceps, may also occur in degenerative meniscal tear cohorts, a group known to have an increased risk of developing OA. In this context, isokinetic dynamometry is one of the most reliable and widespread approaches to assessing muscle strength [16]. Using this approach, we found no significant difference in concentric knee flexor or extensor (body weight adjusted) strength between groups at a velocity of 60 • /s and 180 • /s which can be explained by the rather short duration of the intervention program (6 weeks).…”
Section: Discussionmentioning
confidence: 76%
“…This is why it has been used as a means of muscle strengthening coupled with neuromuscular electrical stimulation intervention [11] in various pathologies of the knee such as gonarthrosis [12], and patellofemoral syndrome [13,14]. The reliability of the test results, notably for lower limb muscles, has enabled isokinetic dynamometers to be regarded as a standard for measuring muscular strength [15,16]. Indeed, isokinetic dynamometers as muscle strength assessment tools for meniscal lesion studies are well-documented [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The isokinetic test has been shown to be a valid and reliable measurement of the strength of the knee flexor and extensor muscles (24). Low angular velocity tests are more accurate in the measurement of muscle strength and high angular velocity tests are used to evaluate the muscle function and endurance (25,26). The tests used in the present study were 60˚/sec and 180˚/sec angular velocity.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, impaired muscle function is usually noticed in patients with OA of the hip and knee [7]. Myers showed that adults with OA have decreased muscle strength and functional capacity [8]. Although, these studies provide insight into the possible muscle strength and functional deficits of this group of adults, they cannot provide convincing evidence, because the subjects were not well matched for variables such as age, body type, physical activity level, and stage of knee OA, each of which would have a significant effect on the process and prognosis of the disease.…”
Section: Introductionmentioning
confidence: 99%